Odpowiedzi

2010-03-24T18:20:37+01:00
2 1/3 * 6 - 3 1/3 : 2 1/6=
=7/3 * 6 - 10/3 : 13/6=
14 - 10/3 * 6/13=
14 - 20/13 = 14 - 1 7/13 = 12 6/13

5 1/4 : 2 1/2 : 1/3=
= 21/4 : 5/2 : 1/3 =
=21/4 * 2/5 : 1/3 =
= 21/10 * 3 = 63/10 = 6 3/10

(12 1/3 - 1/2) * 12 : 1 1/3=
=(37/3 - 1/2)* 12 * 3/4 =
=(74/6 - 3/6) * 9 =
= 71/6 * 9 = 213/2 = 106 1/2
1 5 1
Najlepsza Odpowiedź!
2010-03-24T18:38:54+01:00
2⅓ (razy)6-3⅓ : 2 ¹/₆ = ⁷/₃ (razy)6 - ⁴/₃ : ¹³/₆ =
⁴²/₃ - ⁴/₃ (razy) ⁶/₁₃ = ⁴²/₃ - ⁸/₁₃ = ⁵⁴⁶/₃₉ - ²⁴/₃₉ = ⁵²²/₃₉ = 13 ⁵/₁₃
1 5 1